Selection of genotypes with ornamental potential in an F4 population of ornamental peppers (Capsicum annuum L.) based on multivariate analysis - Costa, Maria Damasceno; do Rêgo, Elizanilda Ramalho; Guedes, Jõao Felipe da Silva; de Carvalho, Michele Gonçalves; da Silva, Anderson Rodrigo; Rêgo, Mailson Monteiro do (Comunicata Scientiae, 2021)
Abstract: The commercialization of ornamental pepper plants has been growing in the national and international floriculture markets. In spite of this growth, there are still few available cultivars for ornamental purposes, suggesting a need for improvement programs in this segment. Given the exposed, this work aimed to select genotypes with ornamental pepper potential using multivariate analysis. The work was performed in a plant nursery at the Campus of Agricultural Sciences of the Federal University of Paraíba (UFPB). One segregating F4 (17.15) population was used, analyzing 16 qualitative and quantitative morphological descriptors. The experimental design was completely randomized. 45 plants belonging to an F4 segregating population were evaluated. Singh’s criterion was adopted to quantify the relative contribution of the characteristics. Afterward, Tocher’s clustering method based on the generalized distance of Mahalanobis was used for the quantitative variables. Gower’s distance was employed for the qualitative variables, and afterward, a joint analysis with qualitative and quantitative data was performed, using the sum of distances of both types of variables. Furthermore, a non-metric multidimensional scaling was applied. Based on qualitative traits 14 clusters were formed. Multidimensional scaling based on quantitative traits the most divergent genotypes were 17, 12, 36, 23, and 19. According to the analysis performed the genotypes 12, 16, 19, 15, 29, 41 and 44 are indicated to open line in F5 generation. Keywords: diversity, gower, Mahalanobis, ornamental plants